2019
DOI: 10.22456/1982-8918.82235
|View full text |Cite
|
Sign up to set email alerts
|

Análisis De Las Características Organizativas De Los Programas De Apoyo a Estudiantes-Deportistas De Élite en El Sistema Universitario De Cataluña

Abstract: Este artigo tem como objetivo analisar as características organizacionais dos programas universitários de apoio à carreira dupla na Catalunha. A amostra foi composta pelas dez universidades que possuíam programas de apoio à carreira dupla. A coleta de dados foi realizada por meio de entrevistas com 13 coordenadores, bem como pela análise do conteúdo existente nos sites web de cada universidade. Os resultados mostram diferentes perfis de alunos-atletas presentes nos programas. Houve deficiências em elementos co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
1
9
0
4
Order By: Relevance
“…In the academic domain, the Spanish legislative framework for facilitating access to a university education for elite athletes was perceived as an important resource, again supporting previous findings (Aquilina and Henry, 2010). Other researchers in Europe have reported that participation in a dual career assistance program is a key resource throughout the transitional period, as it helps participants balance their academic and athletic commitments (Stambulova and Wylleman, 2014;Brown et al, 2015;Geraniosova and Ronkainen, 2015;Mateu et al, 2018b). Tutors as both counselors and mediators are an essential part of these programs (McKenna and Dunstan-Lewis, 2004;Mateu et al, 2018b).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In the academic domain, the Spanish legislative framework for facilitating access to a university education for elite athletes was perceived as an important resource, again supporting previous findings (Aquilina and Henry, 2010). Other researchers in Europe have reported that participation in a dual career assistance program is a key resource throughout the transitional period, as it helps participants balance their academic and athletic commitments (Stambulova and Wylleman, 2014;Brown et al, 2015;Geraniosova and Ronkainen, 2015;Mateu et al, 2018b). Tutors as both counselors and mediators are an essential part of these programs (McKenna and Dunstan-Lewis, 2004;Mateu et al, 2018b).…”
Section: Discussionsupporting
confidence: 73%
“…Other researchers in Europe have reported that participation in a dual career assistance program is a key resource throughout the transitional period, as it helps participants balance their academic and athletic commitments (Stambulova and Wylleman, 2014;Brown et al, 2015;Geraniosova and Ronkainen, 2015;Mateu et al, 2018b). Tutors as both counselors and mediators are an essential part of these programs (McKenna and Dunstan-Lewis, 2004;Mateu et al, 2018b). Nevertheless, it should be noted that at our university, the faculty's teaching staff is not obliged to participate in the dual career assistance program, as lecturers' autonomy prevails over initiatives of this nature in the Spanish university system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual career programs can work as support that provides diversified types of capitals to studentathletes. It can be associated to economic capitals, as the scholarships, or mean to accumulate cultural capitals, as the access to better schools/universities, as well as some kinds of symbolic capitals, when because the legitimate position of elite athlete can make individual be able to alternative means of evaluation and attendance at school (Mateu et al, 2018;Sánchez Pato et al, 2018).…”
Section: The Player's Academic Degree In Adulthoodmentioning
confidence: 99%
“…In addition, the time and actions dedicated to sport does not always can be converted into good conditions and preparation for another labour activity after the termination of athletic career (Alfermann & Stambulova, 2007;Álvarez Pérez & Aguilar, 2012;Damo, 2014;Rigo, Silva, & Rial, 2018). Within this context, many scholars investigated and reflected on the several dimensions that involve the dual career, considering different cultures and possible interventions (Guidotti, Cortis, & Capranica, 2015;Miranda, Santos, & Costa, 2020;Stambulova & Wylleman, 2019) in order to offer adequate conditions to student-athletes be successful both in sport and education (Caput-Jogunica, Ćurković, & Bjelić, 2012;Mateu, Vilanova, & Inglés, 2018;Sánchez Pato et al, 2018), and be prepared to work in another profession in the future (Alfermann & Stambulova, 2007;Stambulova & Wylleman, 2015).…”
Section: Introductionmentioning
confidence: 99%